PENGARUH MEDIA SOSIAL PADA GERNAHA BULAN SUPER BLUE BLOOD MOON - Maliha, Novi Fitia (The Journal of Society and Media, 2018)
Islam responds to natural feomena by presenting a rule of law so that changes that occur in natural phenomena are not a threat or a human life. Lunar eclipse is one of the natural phenomenon that is present at a certain time, not every year occurs and become an interesting natural phenomenon for the community. At this time social media becomes a medium that is effective enough to affect someone against something interesting and rare. The lunar eclipse of 2018 becomes an attraction for the people of the world, one of them Muslim citizens. In general, the lunar eclipse is not known to the public, only astronomers and Islamic?s astronomers can predict it will happen, but the whole eye is interested in seeing the lunar eclipse "super blue blood moon" 2018. The focus of the problem discussed by the author is the lunar eclipse becomes the attraction to be seen massively by the community because of the existence of social media, previously only a solar eclipse that has the attraction to be seen and published. The author uses qualitative research methods with random sampling to the research subjects